Cultivating intercultural communicative literacy through films in language courses (Eurasian Journal of Philology Science and Education, 2023)
In order to enhance intercultural communicative skills and advance language competency in a Kazakh language course, this research examines the potential of films as a medium for language learning. Due to their authentic discourse and rich cultural context, films are being acknowledged as a suitable instrument for language education. Films may give pupils a comprehensive understanding of the language in both its natural usage and cultural context because they are a treasure trove of linguistic and cultural nuances. Our study, conducted within the "Intercultural Communication through Film" course at Nazarbayev University, employed a mixed-methods research design involving a pretest-posttest framework to gauge the effectiveness of film usage in enhancing intercultural communicative competence. The participant pool comprised 45 students from diverse cultural backgrounds and academic majors, providing a broad range of perspectives. A range of data collection tools, including a validated questionnaire and the analysis of reflective essays, was used to measure different aspects of competence. The findings suggest that film-centric assignments stimulate critical thinking, cultural comparisons, and vocabulary enhancement, thereby contributing to a more engaging and effective language learning experience. However, the research also highlights several challenges that must be addressed, including the consideration of varied language proficiency levels and careful film selection to align with the learning objectives. This research contributes significantly to our understanding of film usage in language education, highlighting its potential benefits and challenges. Our findings underscore the need for further research into diverse film genres, varied film-based activities, and the long-term implications of film usage on language proficiency and intercultural competence.